2014
DOI: 10.2147/cia.s64625
|View full text |Cite
|
Sign up to set email alerts
|

Divergent effects of obesity on fragility fractures

Abstract: Obesity was commonly thought to be advantageous for maintaining healthy bones due to the higher bone mineral density observed in overweight individuals. However, several recent studies have challenged the widespread belief that obesity is protective against fracture and have suggested that obesity is a risk factor for certain fractures. The effect of obesity on fracture risk is site-dependent, the risk being increased for some fractures (humerus, ankle, upper arm) and decreased for others (hip, pelvis, wrist).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 57 publications
(96 reference statements)
3
36
0
Order By: Relevance
“…A significant difference in the results of the hip total T score without any difference in the results of the lumber vertebra total T score can be explained by the presence of degenerative processes such as osteoarthritis affecting the results of the vertebra. In addition, several recent studies have suggested that the widespread belief that obesity is protective against fracture and that obesity is a risk factor for certain fractures [28]. In our study BMI was significantly lower in osteoporotic individuals.…”
Section: Discussionsupporting
confidence: 57%
“…A significant difference in the results of the hip total T score without any difference in the results of the lumber vertebra total T score can be explained by the presence of degenerative processes such as osteoarthritis affecting the results of the vertebra. In addition, several recent studies have suggested that the widespread belief that obesity is protective against fracture and that obesity is a risk factor for certain fractures [28]. In our study BMI was significantly lower in osteoporotic individuals.…”
Section: Discussionsupporting
confidence: 57%
“…Also, the precise relationship between weight and fracture rate may depend upon fracture type. Increased weight is generally associated with reduction in osteoporotic fractures (hip and vertebral) but in obese subjects there appears to be an increase in the less common upper arm and ankle fractures (Caffarelli, et al 2014; Compston et al 2011; Mpalaris, et al 2015; Prieto-Alhambra, et al 2012). In general, if weight gain leads to successful skeletal adaptation, as evidenced by an increase in BMD, fracture risk is reduced.…”
Section: Scaling Bone Mass To Body Weightmentioning
confidence: 99%
“…IGF-1) [59]. In the case of high adiposity, which can increase leptin and cortisol, central leptin resistance may mediate the unexpected negative effects of obesity on bone metabolism [62, 63]. Thus, leptin's inhibition of cortisol and glucocorticoids may help to improve bone growth.…”
Section: Leptin's Impacts On Bone Metabolismmentioning
confidence: 99%
“…Obesity caused decreased bone mass density in a controlled study of rats [62]. Obesity may also cause increased fracture risk in humans [63]. Although in the past, it was thought that obesity was protective against osteoporosis and bone fracture risk, new evidence may suggest that obesity, implicated with low-grade inflammation and sarcopenia, may not confer benefits on bone mass [63, 89].…”
Section: Bone Abnormalities In Hypoleptinemia and Leptin Resistancmentioning
confidence: 99%
See 1 more Smart Citation